Extra-small dual-lumen micro-balloon catheters can improve endovascular embolization: an experimental in vivo and in vitro study - Vollherbst, Dominik; Otto, Ruth; Do, Thuy; Deimling, Andreas von; Kauczor, Hans-Ulrich; Bendszus, Martin; Sommer, Christof-Matthias; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2018)
Background The embolization technique can have significant impact on the success of endovascular embolization. - Objective To evaluate the feasibility, embolization characteristics, and embolization extent with a newly developed extra-small micro-balloon catheter in an in vivo and in an in vitro embolization model in comparison with standard microcatheter embolizations. - Materials and methods Twenty-eight embolization procedures were performed in the porcine rete mirabile (RM) and in an in vitro embolization model, using either an extra-small (distal outer diameter 1.6 F) dual-lumen micro-balloon catheter or a standard microcatheter. Precipitating hydrophobic injectable liquid (PHIL) was used as embolic agent. Procedure times, number of injections, required volume of embolic agent, and embolization extent (percentage of embolized RM in postinterventional X-ray scans or number of filled sections of the in vitro model) were assessed. Histopathological analyses were performed. - Results Total procedure time was significantly shorter (in vivo: 123 s vs 615 s (medians), P=0.001; in vitro: 180 s vs 496 s (medians), P=0.001), number of reflux events was significantly lower (in vivo: 0 vs 9 (medians), P=0.001; in vitro: 0 vs 3 (medians), P=0.001), and embolization extent was significantly higher (in vivo: 96.9% vs 65.6% (medians), P=0.011; in vitro: 26 vs 18 filled sections (medians); P=0.041) for the micro-balloon catheter groups. There was antegrade movement of the PHIL cast after balloon deflation in one in vitro embolization procedure and spontaneous balloon deflation with subsequent reflux in one in vivo embolization procedure. - Conclusion Extra-small dual-lumen micro-balloon catheters can improve endovascular embolization in comparison with standard microcatheter embolization.